Evaluation of the quality of standing trees using an Arbotom acoustic stress tomograph - Michajlová Katarína; Gejdoš Miloš; Gergeľ Tomáš; Gretsch Dominik (Central European Forestry Journal)
The assessment of wood quality in forestry operations is crucial for both forestry enterprises and the wood processing sector. Acoustic equipment utilizing excited stress acoustic waves has emerged as a valuable tool for evaluating the internal structure of standing trees. By measuring the propagation speed of these waves within the trunk, it becomes possible to assess the properties of wood before harvesting, aiding in management, planning, and maximizing resource value. The Arbotom acoustic stress tomograph represents one such device designed for evaluating standing trees’ qualitative properties. In a study evaluating its efficacy, 136 trees in a specific forest stand were examined over a period spanning October 2021 to March 2024. The acquired data underwent analysis, with 17 trees selected for qualitative evaluation using both image analysis in ImageJ software and the STN EN 1309-3 standard. The study revealed that, on average, the tomographer tended to overestimate the extent of damage by qualitative features by approximately 14.9% compared to digital image assessment and 9.9% compared to assessment according to the standard. The method could still serve as a component within a broader framework of precision forestry. Combining the acoustic tomography method with other precision forestry techniques could potentially yield more satisfactory results, paving the way for the development of automated systems for assessing tree quality in forest stands. This integration could enhance the efficiency and accuracy of wood quality assessment, benefiting both forestry management and downstream processing operations.